2022
DOI: 10.1177/08862605221130390
|View full text |Cite
|
Sign up to set email alerts
|

Dating App Facilitated Sexual Assault: A Retrospective Review of Sexual Assault Medical Forensic Examination Charts

Abstract: Dating app facilitated sexual assault (DAppSA) is a concerning phenomenon with minimal published research. This retrospective study explored if DAppSAs were different than other sexual assaults (SAs) committed by acquaintances through a review of 3,413 sexual assault medical forensic examination (SAMFE) charts from 2017 to 2020 in a Mountain West state in the United States. Routine Activities Theory and Confluence Model of sexual aggression provided the theoretical framework for the study. Inclusion criteria f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…A story demonstrating that the seemingly innocent Snapchat and adult dating apps — ≥ 18 years age‐restricted — were associated with over three‐quarters of child technology‐facilitated sexual assaults 2 . Our findings are echoed globally — a recent United States‐based study reported one‐sixth of all‐age dating app sexual assault patients in their cohort were 14–17‐year‐old children 3 …”
mentioning
confidence: 66%
“…A story demonstrating that the seemingly innocent Snapchat and adult dating apps — ≥ 18 years age‐restricted — were associated with over three‐quarters of child technology‐facilitated sexual assaults 2 . Our findings are echoed globally — a recent United States‐based study reported one‐sixth of all‐age dating app sexual assault patients in their cohort were 14–17‐year‐old children 3 …”
mentioning
confidence: 66%